Design Innovation and Fashion Cycles - Wolfgang Pesendorfer (American Economic Review, 1995)
A model of fashion cycles is developed in which designs are used as a signaling device in a "dating game." A monopolist periodically creates a new design. Over time the price of the design falls as it spreads across the population. Once sufficiently many consumers own the design it is profitable to create a new design and thereby render the old design obsolete. The paper gives conditions under which all consumers would be better off by banning the use of fashion. Competition among designers may lead to less frequent changes in fashion and to higher prices than monopoly. (JEL D40, L10)